The effects of air pollution on vitamin D status in healthy women: A cross sectional study - Hosseinpanah Farhad; pour Sima; Heibatollahi Motahare; Moghbel Nilufar; Asefzade Saeed; Azizi Fereidoun (BMC, 2010)
Abstract Background Inadequate radiation or insufficient cutaneous absorption of UVB is one of the cardinal causes of vitamin D deficiency. The aim of this study is to determine whether air pollution and low ground level of ultra-violet B light (UVB; 290-315) can deteriorate the body vitamin D status in healthy women. Methods In this cross sectional study 200, free-living, housewives, aged between 20 to 55 years, from Tehran (high polluted area) and Ghazvin (low polluted area) were included. The Tehranian women were selected randomly from participants of the Tehran Lipid and Glucose Study (TLGS) and the Ghazvinian females from patients who came to public health centers. Participants were excluded for disease and drugs which affect vitamin D status and also if they were pregnant or breast feeding. We measured the ground level of UVB using a Haze meter as a surrogate of air pollution. In order to calculate the adjusted mean difference of 25-OH-D, ANCOVA analysis was used. Moreover, Binary logistic regression model was developed to determine the odds of living in Tehran for having serum 25-OH-D less than 20 ng/ml. Results The mean ± SD of serum 25-OH-D was significantly higher in Ghazvinian women ((18 ± 11 vs. 13 ± 7), P-value < 001). The prevalence of 25-OH-D less than 10 ng/ml, and 25-OH-D between 10 and 20 ng/ml were higher in Tehranian group (36% and 54% vs. 31% and 32% in respectively). Secondary hyperparathyroidism was also significantly higher in Tehranian women (47% vs. 32%). In ANCOVA analysis, after adjustment, the mean of 25-OH-D in the Ghazvinian group was still statistically significantly higher than Tehranians (13 vs. 17 ng/ml P-value = 0.04). In addition, in binary logistic model, the odd of living in Tehran for having serum 25-OH-D less than 20 ng/ml was 5.22 (95% confidence interval 2.2-12.2, P-value < 0.001). Conclusion We found that living in a polluted area plays a significant independent role in vitamin D deficiency and hence, residence can be one of the main reasons of vitamin D status of the women.